Immunogenicity and efficacy of oral or intranasal Shigella flexneri 2a and Shigella sonnei proteosome-lipopolysaccharide vaccines in animal models. - Orr, N (1993)
Immunity against shigellosis has been shown to correlate with the presence of antibodies specific for Shigella lipopolysaccharide (LPS). We here propose a new candidate vaccine for shigellosis composed of purified Shigella flexneri 2a or Shigella sonnei LPS hydrophobically complexed with group C type 2b Neisseria meningitidis outer membrane protein proteosomes. Immunization of mice either orally or intranasally with this complex induced specific homologous anti-LPS antibodies in both intestinal and respiratory secretions as well as in sera. Strong anamnestic responses were found after two or three immunizations. LPS alone, alkaline-detoxified LPS, or alkaline-detoxified LPS complexed with proteosomes was not effective. Oral or intranasal immunization of guinea pigs with two or more doses of this proteosome-LPS vaccine elicited homologous protection against Shigella keratoconjunctivitis (Serény test). These data demonstrate that proteosomes can be used as an effective mucosal vaccine delivery system and that orally or intranasally administered acellular vaccines can protect against Shigella infections.